Economic Analysis of Projects - Squire, Lyn; Tak, Herman G. van der; World Bank. (Baltimore : Published for the World Bank [by] Johns Hopkins University Press, 1975)
The book originated from the World Bank, which experimented with the estimation of efficiency and social prices and with their application in the analysis of real-life projects during the late 1970s and early 9180c.
Bibliography: p. 151-153.
osc 13/06/17
Loans
Keywords: Economic development projects; Expenditures, Public